Synthesis and Evaluation of p-Aminobenzoyl hydroxypropyl Cellulose - Khan, Kashif-ur-Rehman; Ovatlarnporn, Chitchamai (Pakistan Journal of Nutrition, 2016)
Hydroxypropyl cellulose (HPC) was selected as a macromolecular carrier for the attachment of para-aminobenzoic acid (PABA) for different pharmaceutical, biomedical and nutritional applications. HPC-PABA ester conjugate was synthesized in a two easy steps that were performed homogeneously. In the first step, the primary amino group of PABA was protected by 98% formic acid and during the second step the protected PABA was coupled with the HPC polymer in DMF by using 4-(dimethylamino)pyridine as a base and N-(3-dimethylaminopropyl)-N-ethylcarbodiimide hydrochloride (EDC.HCl) as a coupling reagent at room temperature. The optimum conditions for deprotection process were also determined. Novel macromolecular conjugate has solubility in both water and organic solvents. HPC-PABA ester conjugate was synthesized with good percentage yield and purity and well identified by FT-IR and 1H-NMR techniques. According to this new synthesis plan HPC-PABA conjugate can be prepared easily and has potential for pharmaceutical, textile and biomedical sectors.